Evaluation of the inclination of maxillary occlusal plane on mounted casts using a fixed value and customized nasion indicator in artex articulator: Facebow system - An in-vivo comparative study - Manikandan Ramasamy; Suma Karthigeyan; T C Giri; Venkateshwaran Rajendran; Adarsh Shetty; Mangala Deivanai (Wolters Kluwer Medknow Publications, 2013)
Aim: To evaluate and compare the variations in the inclination of occlusal plane of casts mounted on Artex articulator using a facebow with a fixed value and customized nasion indicator. Materials and Methods: Twenty two subjects were selected for this investigation. Two maxillary impressions were made, and casts poured. For each of the twenty two subjects, the facebow records were made with, Artex face-bow using a fixed value nasion indicator and customized nasion indicator and mounted. The angle between the occlusal plane of upper cast and the upper articulator arm was measured with a Universal bevel protractor and compared with the gold standard cephalometric value. Results: It shows that, when angle was measured between maxillary occlusal plane and upper member of the articulator, on the mounted cast using a customized nasion indicator and fixed value nasion indicator against the gold standard cephalometric value as a whole, it was found to be not significant. But, if each patient were evaluated individually, there found to be the difference in the angle. Discussion and Conclusion: Variation in occlusal plane was very minimal and close to the cephalometric value when using customized nasion indicator compared to fixed value nasion indicator on the Artex.